Rail passenger knowledge and its impact on information requirements - Kurup, Shalaka (2020)
The rail industry in Great Britain aims to provide value for money by improving customer service and journey satisfaction for passengers, particularly given the rising cost of rail travel. There is increased innovation in several areas, including the personalisation of information, automatic delay repayment, the provision of on-board Wi-Fi, and importantly, the successful management of disruption. The enhancement of disruption information is a key area of investment and research within the industry. The aim of this project was to investigate the current landscape of information provision during rail travel with a focus on increasing its appeal to all passengers, principally during disruption. Specifically, the main objective was to understand how academic theories of expertise and passenger behaviour can aid in improving the design of the content and delivery of rail information to passengers. Following the review of existing research around information provision and passenger experience, interviews were conducted with both rail passengers and service providers to discuss the main themes found in the literature. The aim was to gain an understanding of the main challenges surrounding information provision, particularly with regards to adapting to differing levels of customer knowledge. It was noted that there were key differences seen – both from the literature and the interviews – between frequent and infrequent travellers, which could be attributed to being a product of extensive travel experience, or expertise. At this point, the first step taken was to investigate these differences in a large-scale manner, with a specific focus on the way in which knowledge and experience impacted information use. For this purpose, three different types of surveys were designed and administered. The first, an online survey, was used to examine the information preferences of travellers, alongside their assessments of their own level of expertise regarding rail journeys, and their travel frequency. Results showed that expertise and travel frequency seemed to only account for some of the variance in the preferences for different types of rail information. However, rail information was grouped into six distinct categories according to participant ratings, with some types of information being rated significantly higher than others. This was followed by a repertory grid study and an online survey. This study aimed to look at expertise and travel frequency as well, but with an examination of disruption support, as opposed to generalised rail information. Results confirmed the distinct differences between self-rated expertise and ratings of travel frequency – while most people seemed to consider themselves as being fairly knowledgeable regarding rail travel, there were clearer differences seen with regards to the more objective assessment of their travel frequency. Particularly, frequent travellers understand the nuances of disruption information better – identifying both “good” and “bad” features of disruption alerts – as opposed to less/infrequent travellers, who only focused on the uncertainty created by the disruption alerts. Additionally, four important characteristics of disruption information were identified. The final survey – a vignette experiment – aimed to look at expertise and frequency, in addition to other aspects of rail travel. The aim was to identify the impact of other factors that could be contributing to information use and disruption management. Two variables were selected: journey purpose and the level of familiarity that one has with their trip. Hypothetical disruption scenarios were presented to participants, with the variation of these factors. This was followed by the rating of the six main types of rail information gathered from the online survey, and the four key disruption characteristics obtained from the repertory grid survey. These were rated based on their “usefulness” within the hypothetical disruption situation. The findings were surprising. There was limited influence of the variables examined, with distinct preferences for specific types of information seen across all passengers, regardless of the factors presented, or their expertise or travel frequency. When it comes to disruption management, it seems to be that everyone’s preferences for informational support are the same. The main theoretical impact of this thesis was with regards to the study of expertise in itself. Expertise, simply put, is hard to study. Travel frequency, on the other hand, is not. This thesis contributes evidence towards the notion of expertise being a product of experience and practice, making frequency of travel an appropriate proxy for the study of expertise within dynamic travel environments. From an industry perspective, these findings led to the development of an information provision template that outlines the basic areas to be covered when presenting information to rail passengers, within both general travel situations, as well as during the occurrence of a disruptive event. This template can be used as a guidance checklist for the development of all forms of information systems, from mobile applications to on-board information screens to station displays. This thesis concludes with recommendations for the application of these findings, and for future research within this area.